KETIDAKBERPIHAKAN JARGON POLITIK TERHADAP PEREMPUAN DI INDONESIA - Rosida Tiurma Manurung (Fakultas Seni Rupa dan Desain ITB, 2009)
It has become a reality that a woman is the second class citizen in the society. The role of the woman had not been counted on. In the field of education, economics, social, religious conviction, also politics, woman has always been gazed at an eye. Furthermore, the woman is the creature who has always been set aside in the world of politics. In the matter of political jargon, the woman did not get the place, did not have the right, and her role was stunted. Development of political jargon today really does not take sides with the woman. Jargon like